Additive manufacturing technology: mapping social impacts. Issue 1 (29th August 2018) - Matos, Florinda; Jacinto, Celeste
Abstract : Purpose: Recent developments in additive manufacturing (AM) technology have emphasized the issue of social impacts. However, such effects are still to be determined. So, the purpose of this paper is to map the social impacts of AM technology. Design/methodology/approach: The methodological approach applied in this study combines a literature review with computer-aided content analysis to search for keywords related to social impacts. The content analysis technique was used to identify and count the relevant keywords in academic documents associated with AM social impacts. Findings: The study found that AM technology social impacts are still in an exploratory phase. Evidence was found that several social challenges of AM technology will have an influence on the society. The topics associated with fabrication, customization, sustainability, business models and work emerged as the most relevant terms that can act as "pointers" to social impacts. Research limitations/implications: The research on this subject is strongly conditioned by the scarcity of empirical experience and, consequently, by the scarcity of data and publications on the topic. Originality/value: This study gives an up-to-date contribution to the topic of AM social impacts, which is still little explored in the literature. Moreover, the methodological approach used in this work combines bibliometrics with computer-aided content analysis, which also constitutes a contribution to support future literature reviews in any field. Overall, the results can be used to improve academic research in the topic and promote discussion among the different social actors.